Kajian Literatur: Implementasi Advanced Care Directives Di Asia - Claudia Adreina Refo; Dinda Kartianty Harefa; Widya Lestari Ralendesang; Yenni Ferawati Sitanggang; Kinanthi Lebdawicaksaputri (Malahayati Nursing Journal, 2022)
ABSTRACT Advance Care Directives (ACD) is a plan made by individuals regarding future care services. ACD can guide care, improve the quality of communication and patient life and reduce unwanted care in the hospital. The purpose of this literature review is to see an overview of how nurses implement ACD in Asian countries. This literature review uses the method of thematic analysis: a simplified approach which is described simply. Data search use three databases such as PMC, EBSCO, and ScienceDirect with the use of Boolean operators AND and OR. Using PRISMA flow diagrams for the article selection process. The article/data analysis carried out using the Critical Appraisal Checklist tools developed by the Joanna Briggs Institute (JBI). The implementation of ACD in Asia has been carried out in countries such as China, Hong Kong, Taiwan, Japan, Singapore and Korea. In the article analysis, ACD implementation can be described in three themes: the implementation of ACD by nurses, the benefits of ACD that are felt by patients, families and nurses and factors that influence nurse implementation. ACD was seen to be crucial for patients in facilitate their wish and needs. Even though physician was the one who initiate the ACD implementation, nurses still play their role as an educator, advocate and also facilitator in the process of ACD implementation. Keyword: Advance Care Directives, Advance Care Planning, Nurses, Asia, Implementation  ABSTRAK Advance Care Directives (ACD) adalah sebuah rencana berisi tentang pelayanan perawatan dimasa depan yang dibuat oleh individu. ACD bertujuan untuk meningkatkan kualitas komunikasi dan hidup pasien serta mengurangi perawatan yang tidak diinginkan di rumah sakit, serta menjadi petunjuk dalam menjalankan perawatan. Studi literatur ini bertujuan untuk menggambarkan tentang pelaksanaan ACD di negara-negara Asia.  Kajian literatur ini menggunakan metode thematic analysis: a simplified approach. Tiga database digunakan dalam pencarian artikel antara lain; PMC, EBSCO, dan ScienceDirect. Penulis menggunakan Boolean operator AND and OR dalam pencarian. Diagram prisma digunakan untuk menjelaskan proses pencarian artikel yang selanjutnya analisis artikel/data dilakukan menggunakan Critical Appraisal Checklist tools yang dikembangkan oleh Joanna Briggs Institute (JBI). Pelaksanaan ACD di Asia dilakukan di beberapa negara seperti Cina, Hong Kong, Taiwan, Jepang, Singapura, dan Korea. Dalam analisis artikel ditemukan bahwa pelaksanaan ACD Implementasi tersebut digambarkan dalam bentuk inisiasi pelaksanaan ACD, manfaat ACD yang dirasakan oleh pasien, keluarga serta perawat dan faktor yang mempengaruhi pelaksanaan ACD. ACD dinilai sangat penting untuk memfasilitasi keinginan dan harapan pasien. Meskipun pelaksanaan ACD di inisiasi oleh dokter, perawat tetap berperan sebagai edukator, advokat dan fasilitator selama proses pelaksanaan ACD. Kata Kunci: Advance Care Directives, Advance Care Planning, Nurses, Asia, Implementation